Inhibition of oocyte development in Japanese medaka ( Oryzias latipes) exposed to di-2-ethylhexyl phthalate - Kim, Eun-Joo; Kim, Jung-Wk; Lee, Sung-Kyu (Environment international, 2002)
Di-2-ethylhexyl phthalate (DEHP) is a widely used plasticizer known to be a suspected endocrine disrupter, but its precise effects on aquatic organisms are not yet known. When Japanese medaka ( Oryzias latipes) were exposed from the time of hatching to 3 months of age to an aqueous DEHP solution at nominal concentrations of 1, 10, and 50 μg/l, DEHP-treated female fish showed distinct reproductive effects as follows. First, blood vitellogenin levels in all treated test subjects markedly decreased. Second, Gonado Somatic Index (GSI) decreased to 33% and 38% of the control GSI in 10 μg/l and 50 μg/l treated female fish, respectively. Third, 54% of female fish in the control treatment had completely matured oocytes in their ovaries, but only 37%, 0% and 22% of female fish matured to the last stage in the 1, 10 and 50 μg/l treated test subjects, respectively. Unlike female fish, no change or adverse effects were observed in the male fish. In summary, DEHP hinders the development of reproductive organs in the female Japanese medaka. In this work, the possibility of anti-estrogenic activity of DEHP is proposed as the cause.